The loss of rural vital places: A case study using the social determinants of health framework - Danielle Rhubart; Jennifer Kowalkowski; Hazel Velasco Palacios; Kristina Brant (Wellbeing, Space and Society)
Healthy food sources, recreational facilities, and social spaces serve as vital places for supporting health. Less is known about what happens when vital places are lost, especially in rural contexts that have experienced disinvestment and population decline. In this paper we use a case study of a small rural community in Pennsylvania that lost a substantial share of its vital places over a short period of time to explore the experiences of local residents. Using qualitative interviews with 26 local residents we show that the loss of vital places, which are part of the neighborhood and built environment, intersected with other social determinants of health with potential consequences for health and well-being. This was often because vital places were essential (i.e., few or no alternatives existed) and multifunctional (i.e., supporting health through multiple behavioral and social mechanisms). Examining experiences of local residents following the loss of vital places through a social determinants of health lens helps to identify consequences and inform adaptation strategies. We also use the findings to refine the vital places framework for rural contexts.